2018
DOI: 10.3389/fmicb.2018.01787
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Activity of Lactic Acid Bacteria Combinations in Dairy Mimicking Models and Their Potential as Bioprotective Cultures in Pilot Scale Applications

Abstract: Consumer's demand for naturally preserved food products is growing and the use of bioprotective cultures is an alternative to chemical preservatives or a complementary tool to hurdle technologies to avoid or delay fungal spoilage of dairy products. To develop antifungal cultures for the dairy product biopreservation, experiments were conducted both in vitro and in situ. Firstly, the antifungal activity of 32 strains of lactic acid bacteria (LAB) and propionibacteria was screened alone, and then on combinations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(34 citation statements)
references
References 44 publications
1
31
0
1
Order By: Relevance
“…All ten strains examined have homologs of pore-forming toxins (PFTs), although most of these toxins, prevalent in the lactobacilli, are bacteriocins. Many of the toxins identified in the strains have antifungal properties; the antifungal effects of lactobacilli have been studied in some detail [ 88 , 89 , 90 ]. Some of the toxic proteins, however, have pathogenic effects on mammalian cells.…”
Section: Discussionmentioning
confidence: 99%
“…All ten strains examined have homologs of pore-forming toxins (PFTs), although most of these toxins, prevalent in the lactobacilli, are bacteriocins. Many of the toxins identified in the strains have antifungal properties; the antifungal effects of lactobacilli have been studied in some detail [ 88 , 89 , 90 ]. Some of the toxic proteins, however, have pathogenic effects on mammalian cells.…”
Section: Discussionmentioning
confidence: 99%
“…Probiotics isolated from traditional dairy products comprise species of lactic acid bacteria with a history of safe use. The employment of live bacteria incorporated in food is included in the European Qualified Presumption of Safety list (Leyva Salas et al., 2018). Many probiotic lactic acid bacterial strains isolated from different dairy products have also undergone review and testing and have fulfilled the FDA “GRAS” status for use in fermented dairy product and other food items.…”
Section: Introductionmentioning
confidence: 99%
“…Using the overlay method, several studies have found different species of LAB to have strong antifungal activity. This includes Inglin et al (2015) , who reported both antifungal and antibacterial activity of LAB species; Garnier et al (2018) , who found that Mucor racemosus and P. commune could be inhibited by certain L. rhamnosus and L. plantarum cultures, and Salas et al (2018) , who found that a mixture of Lactobacillus harbinensis ( L. harbinensis ) and L. plantarum exhibited inhibitory effect on Mucor and Penicillium strains.…”
Section: Discussionmentioning
confidence: 99%